Basaloid squamous cell carcinoma of the uterine cervix coexisting with undifferentiated sarcoma - Lemm, Magdalena; Słowik, Łukasz; Cichoń, Bartosz; Poński, Michał; Szwaczka, Łukasz; Bakon, Igor; Witek, Andrzej (Menopause Review/Przegląd Menopauzalny, 2020)
Basaloid squamous cell carcinoma is uncommon tumor and has received little recognition, there are only a few cases in the medical literature. Correct diagnosis is important due to the high malignancy of this cancer and poor prognosis. We present a rare and interesting case of a basaloid squamous cell carcinoma of the uterine cervix in a 71-year-old female with prolapse of the uterus with co-existing atypical undifferentiated sarcoma.